Evaluating Alternate Visualization Methods for Microsurgery: 2D and 3D Optical Microscopes and Flat-Panel Displays - Sackllah, Michael; Yu, Denny; Woolley, Charles; Kasten, Steven; Armstrong, Thomas J. (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2012)
Due to the inherent postural constraints from a microscope, surgeons who perform minimally invasive surgeries may be exposed to prolonged static postures. As 3D displays become more economically viable, their role in the healthcare industry may become more prominent. The purpose of this pilot-study is to assess the effect of stereoscopic displays on postural constraint, perceived effort, and performance during simulated microsurgery tasks. Ten subjects with no surgical experience performed microsurgical skills tests using four visualization methods: 2D flat panel display, 3D flat panel display, monoscopic microscope, and stereoscopic microscope. Body posture was measured via motion tracking equipment and task performance was captured through video analysis. Subjective data was gathered on posture, perceived effort, and equipment usability. Significant differences were found between all displays for each measured joint angle; however, all posture deviations can be classified as neutral. Participants were unable to perceive posture differences between the visualization methods. Task completion times were fastest for the monoscopic microscope; however, the differences were not significant. Total errors were significantly greater for the monoscopic microscope than the flat panel displays. Perceived effort ratings were not significantly different among visualization methods. This study demonstrates that 2D and 3D flat panel visualization methods may provide an alternative to microscopes during surgery; however, hardware improvements are needed before this technology is viable in the healthcare industry.